Generating new magnetic properties in organic–inorganic hybrids. Issue 7 (3rd February 2017) - Wu, J.; Akhtar, N.; Gengler, R. Y. N.; Palstra, T. T. M.; Rudolf, P.
Abstract : Organic–inorganic hybrids are a rapidly developing class of multifunctional materials, which can present properties different from those of either of their building blocks. Abstract : Organic–inorganic hybrids are a rapidly developing class of multifunctional materials, which can present properties different from those of either of their building blocks. Control over the structure during the assembly process is crucial to achieve the desired functions. Here we present the layer-by-layer deposition in ambient conditions of CoCl4 -octahedra or MnCl4 -octahedra and organic layers to tailor their magnetic properties. The Langmuir–Blodgett technique used to assemble these structures provides intrinsic control over the film structure down to the molecular level. Magnetic characterization reveals that MnCl4 -based hybrid Langmuir–Blodgett films order antiferromagnetically like the bulk hybrid, while the CoCl4 -based hybrid Langmuir–Blodgett films show ferromagnetic coupling in contrast to the bulk hybrid, which is a paramagnet.